Indicators of Social Performance: Between Efficiency and Legitimacy - Amifi, Hamid; Benlakouiri, Abderrahim (International Journal of Engineering and Technology, 2019)
This communication studies the social performance (SP). We were able to build an explanatory model that identifies the determinants of the use of SP indicators and spot the real motivation of the company to use them as a control device and Management: Is it to meet a need for effectiveness and efficiency, or rather to have greater legitimacy? The first category of assumptions is related to the contingent theory. These assumptions explain the use of Social indicators for the company's willingness to be more effective and efficient. The second category of assumptions is related to neo-institutional theory. These assumptions explain the use of Social indicators by the willingness of the company to sit its legitimacy in its institutional environment and, above all, to have the confidenceÂ Â